Green Roofs as a Sustainable Building Practice: A Lab-Scale Evaluation Using Recycled Waste Materials for Stormwater Runoff Control - Romali, Noor Suraya; Shifa’ Mawaddah Kamarul Zamani; Dayang Arnieza Penni; Wan Syuaibah Wan Zaki; Sumiliana Sulong (International Journal of Integrated Engineering, 2025)
Sustainable building in Malaysia is gaining momentum as developers increasingly adopt eco-friendly practices to mitigate environmental impact and promote long-term sustainability in response to rapid urbanization and climate challenges. Green roofs play a crucial role in the sustainable building movement by enhancing insulation, managing stormwater, and supporting biodiversity. Despite these benefits, green roofs remain rarely adopted in Malaysia. Thus, the objective of this study is to evaluate the performance of green roofs for stormwater control by testing two laboratory-scale models utilizing: (i) commercial materials and (ii) recycled waste materials. The findings revealed that green roofs significantly reduced stormwater runoff compared to conventional roofs, with green roofs with recycled materials achieved up to 72% peak flow reduction, exceeding the performance of those with commercial materials, which achieved up to 54% reduction. Thus, green roofs can contribute to sustainable development by managing stormwater effectively, and the incorporation of recycled materials enhances the performance of a green roof but also lowers construction costs, making sustainable practices more economically viable for developers and builders.